Salafi Dakwah and the Dissemination of Islamic Puritanism In Indonesia: A Case Study of the Radio of Rodja - Ayang Utriza Yakin (Universitas Islam Negeri Mataram, 2018)
The article examines Islamic proselytization (dakwah) on Rodja Radio by Salafi preachers (dai). The radio program targets not only Salafis but also non-Salafi Muslims in general. It seeks to analyze the content of dakwah aired by Radio Rodja 756 AM., the leading Salafi radio station located in Cileungsi, Bogor, West Java. This article focuses mainly on current legal, social, and political issues of the Salafi dakwah. The dakwah aired by Rodja Radio intends to encourage the Muslim ummah to return to the way of life that strictly follows the tradition of the Prophet Muhammad and the first three generations of Muslims. The Salafi radio station propagates Islamic puritanism that in many ways contradicts modern values. Rodja Radio preachers demonstrate their reluctance to embrace modern ideas, such as democracy, human rights, women’s rights, and to some extent, art and education. This article reveals that the radio serves as a public sphere where the Salafis disseminate ‘Islamic Puritanism’ on Indonesian air.